Spontaneous mutation results in lower cellulose production by a Gluconacetobacter xylinus strain from Kombucha - Nguyen, V.; Flanagan, B.; Mikkelsen, D.; Ramirez, S.; Rivas, L.; Gidley, M.; Dykes, Gary (Elsevier, 2010)
This study aimed to investigate the characteristics of a spontaneous mutation that results in lower cellulose production by a Gluconacetobacter xylinus strain isolated from Kombucha. The growth of this mutant was initially observed in Hestrin Schramm (HS) static and agitated cultures but not in modified (higher nutrient) HS cultures, indicating different nutrient conditions may play a role in the selection of the spontaneous mutant. The mutant produced a significantly (P < .05) lower amount of cellulose than the wild-type in HS static culture. Nuclear magnetic resonance and scanning electron microscopy indicated that the cellulose produced by the mutant had the same crystalline structure as that produced by the wild-type but had a lower density of fibrils. Two-dimensional gel electrophoresis of total proteins demonstrated the presence of the enzyme deoxythymidine diphosphate (dTDP)-4-dehydrorhamnose 3,5-epimerase in the mutant but not in the wild-type. This enzyme could be involved in the synthesis of acetan, which may reduce cellulose synthesis and be the basis for the characteristics of the mutant. © 2010.